2009
DOI: 10.1111/j.1365-3156.2009.02396.x
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐modal Aedes aegypti mosquito reduction interventions and dengue fever prevention

Abstract: Summaryobjective To systematically review the effectiveness of biological, chemical and educational dengue fever prevention programs on the reduction of entomologic indicators.methods Searches of PubMed, GoogleScholar, CabDirect databases and reference lists yielded over 1000 articles containing mosquito abatement interventions. Inclusion criteria were: Vector control programs targeting Aedes aegypti and Aedes albopictus mosquitoes; Studies providing pre-and post-test data. Intervention effectiveness was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 32 publications
3
59
0
2
Order By: Relevance
“…The latter should not be a surprise, given the little evidence on the effectiveness of the building blocks of such programs, be it (peri-) domestic spraying against adult mosquitoes 24 or chemical and biological interventions targeting immature stages. 25 Erlanger and others 26 ventured a meta-analysis and found, in an array of controlled studies of variable quality, a more than 3-fold reduction in Breteau index with chemical control combined with environmental management. For ITC, Kroeger and others 12 imputed a 2.5-to 3-fold decrease in the pupae per person index at 9 and 12 months in Venezuela and Mexico, respectively, but could not fully control for temporal trends.…”
Section: Discussionmentioning
confidence: 99%
“…The latter should not be a surprise, given the little evidence on the effectiveness of the building blocks of such programs, be it (peri-) domestic spraying against adult mosquitoes 24 or chemical and biological interventions targeting immature stages. 25 Erlanger and others 26 ventured a meta-analysis and found, in an array of controlled studies of variable quality, a more than 3-fold reduction in Breteau index with chemical control combined with environmental management. For ITC, Kroeger and others 12 imputed a 2.5-to 3-fold decrease in the pupae per person index at 9 and 12 months in Venezuela and Mexico, respectively, but could not fully control for temporal trends.…”
Section: Discussionmentioning
confidence: 99%
“…A review of 21 studies comparing biological, chemical and educational dengue prevention programs found that biological interventions were the most effective; nearly all the biological interventions eliminated mosquito larval populations, whereas the chemical interventions were judged to be the least effective, and were not thought to offer a long-term solution (Ballenger-Browning and Elder, 2009). A separate review of 56 field studies found that the relative effectiveness of biological control was better than chemical or environmental/physical control measures, but that an integrated approach was best (Erlanger, et al 2008).…”
Section: Potential Of Biological Control Methods In the Futurementioning
confidence: 99%
“…Sus objetivos incluyen: estrategias de comunicación masiva; sensibilización intersectorial, fortaleciendo redes organizacionales; el fortalecimiento de los sistemas de vigilancia y monitoreo, el desarrollo de entornos saludables a fin de reducir los índices de infestación a través de diversas actividades; como en el recojo oportuno y adecuado de residuos sólidos e inservibles, fumigaciones y promoviendo la educación sanitaria 11 . Sin embargo, la efectividad de las estas intervenciones, depende de su continuidad, cobertura, y principalmente de la ejecución de conductas preventivas continuas por parte de la comunidad 12 . Esta ejecución está influenciada tanto de las percepciones individuales y colectivas sobre el riesgo a la enfermedad, como del reconocimiento de la vulnerabilidad según las condiciones de saneamiento en las que las personas viven.…”
Section: Introduccionunclassified